الفنون الصحفية في صحيفة (تێگەیشتنی ڕاستی) - حسين, د.باقر داود (Sulaimani Journal for Humanities, 2021)
This research deals with the development of journalistic arts in the newspaper (Tigashtni Rasti), which is considered a qualitative leap in the history of the Kurdish press, as this newspaper, due to reasons that will become clear in the course of the research, is a qualitative leap in the course of the Kurdish press, in terms of its interest in journalistic arts on its pages. On the pages of this newspaper, journalistic arts that had not appeared before in the Kurdish press appeared, such as the art of interviewing and the art of investigative journalism. It also paid great attention to the art of journalistic news in a way that it had never before experienced in the Kurdish press, as the Kurdish press before (Tigashtni Rasti) was opinion journalism and did not care about the news except in a slight way, while this newspaper devoted a large area of its pages to the news, which helped it to obtain this On those news from a well-established news agency, Reuters, which belongs to the same country that issued (Tigashtni Rasti), namely the State of Britain, which is considered one of the oldest countries in issuing newspapers. This research, based on its perspective, deals with the fundamentals of (the method of content analysis), the journalistic arts that were used in the newspaper (Tigashtni Rasti) and the fields in which those arts were used. This is by obtaining field answers to the following questions: What are the journalistic arts that have been published in the newspaper (Tigashtni Rasti)? What are the fields in which these journalistic arts were published? The research is considered descriptive research suitable for this type of media field, and on the method of content analysis. The press material published on the pages of the newspaper (Tigashtni Rasti) was analyzed in all its numbers. Among the most important findings of the research are: 1. this newspaper was a news newspaper par excellence. 2. Most of the news was international news, 3. The newspaper was the first Kurdish newspaper to publish photographs on its pages.